If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 = x + -7 Reorder the terms: -7 + 2x = x + -7 Reorder the terms: -7 + 2x = -7 + x Add '7' to each side of the equation. -7 + 7 + 2x = -7 + 7 + x Combine like terms: -7 + 7 = 0 0 + 2x = -7 + 7 + x 2x = -7 + 7 + x Combine like terms: -7 + 7 = 0 2x = 0 + x 2x = x Solving 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 1x = x + -1x Combine like terms: x + -1x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| T/15=5 | | x(x+2x+x(x-1)+1-4)=0 | | u=2x-5 | | 15-2x=10-5x | | 6(-2+a)-(-5+a)-3(9+a)=0 | | 3n+7-n-3=n | | 6p+1=3[2p+1] | | P=(5t/6)-4 | | 5t+11=5 | | 6a+3b+c=-23 | | (-8)/(-1)/(1)/(4) | | 3[g-1]-7=3g+4 | | 55x+15=.65x+50+75 | | 55x*15=.65+50+.75 | | 457m=356765 | | (w-7)(w+2)= | | 3x+2x+x=168 | | 0.2222222220+01.4444444444(x)=50.8+-2.9(x) | | (X^2+8x+16)*(5x+9)= | | 7/8t=-8 | | 17(x+6)(4x+3)=0 | | (600-5y)+(142.5)=30 | | -1=-4b-1-3b | | 7+(2y+17)=-2 | | 3/5d-4/5=1/3D | | 40x*.45+50x*.55= | | 12x-3(x+4)=5x+20 | | 2486=2m | | 5-3k-2k=20 | | a/4-a/7=-6 | | 10.56/4.4= | | (m-5)-5=8-2(m-4) |